The vertical position during labor: pain and satisfaction Posição vertical durante o trabalho de parto: dor e satisfação - Maria Amelia Miquelutti; Jose Guilherme Cecatti; Sirlei Siani Morais; María Yolanda Makuch (Instituto Materno Infantil de Pernambuco, 2009)
OBJECTIVES: to evaluate the vertical position adopted by nulliparous women during labor in terms of pain and satisfaction with the position. METHODS: the study was based on a secondary efficacy analysis of data from 107 nulliparous women enrolled in a randomized controlled trial in which the vertical position adopted during the dilation phase of labor was evaluated. The analysis involved comparing the median percentages of the duration for which women remained in the vertical position for each of the variables studied . The Kruskal-Wallis and Mann-Whitney tests were used to determine the difference s betwee n th e groups. Statistical significance was set at p<0.05. RESULTS: at 4cm of dilation , the women with a pain score < 5 remained longer in the vertical position during labor compared to those with a score > 7 (p=0.02) . At 4 and 6 cm of dilation , the women who reported greater satisfaction remained more than 50 % of the time in the vertical position (p=0.0 2 an d p=0.03 , respectively). CONCLUSIONS: the vertical position helped relieve labor pain and increased comfort and patient satisfaction. OBJETIVOS: avaliar a posição vertical , adotada por mulheres nulíparas durante o trabalho de parto , em relação à dor e satisfação com a posição. MÉTODOS: abordagem analítica distinta, complementar e de eficácia de 107 nulíparas, secundária aos dados de um ensaio controlado randomizado, que avaliou a posição vertical em nulíparas durante a fase de dilatação do trabalho de parto. A análise foi realizada pela comparação das porcentagens medianas do tempo de permanência na posição vertical para cada categoria das variáveis estudadas. Para testar as diferenças entre as variáveis foram utilizados os testes de Kruskal-Wallis e de Mann-Whitney. A significância foi estabelecida em p<0.05. RESULTADOS: aos 4 cm de dilatação , as mulheres que apresentaram escore de dor < 5 permaneceram maior tempo do trabalho de parto na posição vertical quando comparadas às que tiveram escore > 7 (p=0.02). As mulheres mais satisfeitas, aos 4 e 6 cm de dilatação, permaneceram mais de 50 % do tempo na posição vertical (p=0.0 2 e p=0.03, respectivamente). CONCLUSÕES: a posição vertical auxiliou no alívio da dor , melhorou o conforto e satisfação das parturientes.